Breast Cancer Awareness among Female School Teachers of Selected Schools of Gokarneswor Municipality, Kathmandu (Nepal Medical College Journal, 2024)
Breast cancer (BC) has become the most diagnosed cancer globally, in the year 2020. It has emerged as major global health challenge affecting women in low- and middle-income countries including Nepal. Teachers play an effective role in communication and motivation of young students, assessment of their awareness is essential to reduce the risk of breast cancer among future young generations Therefore, this study was carried out to find out breast cancer awareness among female school teachers of selected schools of Gokarneswor Municipality, Kathmandu. A descriptive cross-sectional study was conducted among 220 female school teachers of conveniently selected 9 different government and private schools of Ward 4, 8, 9 of Gokarneswor Municipality from July 2023-October 2023. Total enumerative census sampling technique was used to collect the data, SPSS version 16 was used for data entry and analysis. Descriptive statistics such as median, frequency and inferential statistics such as chi-square tests were used. The study revealed majority (72.8%) of respondents were below age group of 40 years. Nearly half (45.9%) of the respondents had bachelor degree of education. Majority (80.1%) of the respondents were working in the private schools and nearly half (59.1%) had teaching experience more than 10 years. Nearly half (46.8%), were aware that obesity, use of oral contraceptives (43.6%) were risk factors and more than half (60%) knew that not breast feeding was risk factors for breast cancer. Most of the respondents (92.7%), were aware that presence of breast lump is the sign/symptoms of breast cancer. Level of awareness was high in (53.2%) of respondents. Significant association was found between level of awareness and level of education (p=0.007) and type of school (p=0.014). Level of awareness was found to be low in nearly half (46.8%) of the respondents. In the present study awareness about breast cancer among the study participants is still needed to be increased. The magnitude of breast cancer disease burden is expected to increase without awareness and preventive interventions. Intense health education campaign should be conducted at regular intervals regarding the importance of screening methods for the prevention of breast cancer.